The Prognostic Value of the Prognostic Nutritional Index (PNI) in Radically Resected Esophagogastric Junction Adenocarcinoma. (31st December 2021) - Ge, Kele; Fang, Cheng; Zhu, Danxia; Yan, Haijiao; Wang, Qi; Chen, Wenyu; Wu, Jun
Abstract: To determine the influence of preoperative prognostic nutritional index in adenocarcinoma of the esophagogastric junction, this study was conducted to analyze 420 patients with adenocarcinoma of the esophagogastric junction who underwent surgery. A total of 120 healthy volunteers were included as the healthy control group. The cutoff values of prognostic nutritional index for predicting survival were obtained according to the receiver operating characteristic curve. The clinic-pathological feature and survival were compared between low and high prognostic nutritional index group. Results showed that the prognostic nutritional index in the patient group was lower than that in the healthy control group ( P  < 0.05). The level of prognostic nutritional index was significantly associated with tumor differentiation, Siewert type, tumor size, body mass index, and hemoglobin levels ( P  < 0.05). The level of prognostic nutritional index was negatively correlated with age of onset, tumor differentiation, Siewert type, tumor size, depth of tumor, but positively associated with the levels of body mass index and hemoglobin. Multivariate analysis revealed that prognostic nutritional index was an independent factor associated with disease-free survival ( P  = 0.027) and overall survival ( P  = 0.003). In conclusion, low prognostic nutritional index may be considered as an independent adverse prognostic marker in patients with adenocarcinoma of the esophagogastric junction.